2017
DOI: 10.1080/15321819.2017.1329152
|View full text |Cite
|
Sign up to set email alerts
|

Significance of pregnancy test false negative results due to elevated levels of β-core fragment hCG

Abstract: Very high levels of β-core fragment human chorionic gonadotrophin (βcf-hCG) are reported to potentially cause false negative results in point-of-care (POC)/over-the-counter (OTC) pregnancy tests. To investigate this further, women's daily early morning urine samples, collected prior to conception and during pregnancy, were analysed for intact, free β-, and βcf-hCG. The proportion of βcf-hCG was found to be related to that of hCG produced and in circulation. Therefore, best practice for accuracy testing of POC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Testing highly contaminated samples by sandwich format LFIA can lead to the so-called 'hook-effect' [150], which cannot be reliably identified by the naked eye alone. The hook-effect can lead to false-negative results even in a laboratory [151], but it has been demonstrated in a selected number of LFIAs that this high antigen concentration effect can be identified experimentally by smartphone video processing [152,153].…”
Section: Sensitivity Specificity and Robustnessmentioning
confidence: 99%
“…Testing highly contaminated samples by sandwich format LFIA can lead to the so-called 'hook-effect' [150], which cannot be reliably identified by the naked eye alone. The hook-effect can lead to false-negative results even in a laboratory [151], but it has been demonstrated in a selected number of LFIAs that this high antigen concentration effect can be identified experimentally by smartphone video processing [152,153].…”
Section: Sensitivity Specificity and Robustnessmentioning
confidence: 99%
“…1,6 βcf-hCG levels begin rising above intact hCG levels in the urine at around 7 weeks' gestation, attaining a 2.8-fold increase at 8 to 14 weeks' gestation. 7 Although variant hook effect is most likely to occur after 8 to 14 weeks' gestation, false-negative urine hCG test results can occur as early as 6 weeks' gestation. One study examining 11 760 urine hCG test results showed 40 falsenegative results (0.34%), with 22 (0.19%) likely due to βcf-hCG.…”
Section: Variant Hook Effectmentioning
confidence: 99%
“…Variant hook effect occurs when one antibody with an affinity for βcf-hCG becomes saturated while the other antibody does not recognize βcf-hCG, causing a false-negative result . βcf-hCG levels begin rising above intact hCG levels in the urine at around 7 weeks’ gestation, attaining a 2.8-fold increase at 8 to 14 weeks’ gestation . Although variant hook effect is most likely to occur after 8 to 14 weeks’ gestation, false-negative urine hCG test results can occur as early as 6 weeks’ gestation.…”
Section: Test Characteristicsmentioning
confidence: 99%
“…[5,6] The pattern of appearance and concentration increase of hCG that occurs in the maternal circulation has similarly been shown in the urine of pregnant women. [3,7,8] There are numerous home pregnancy tests currently available on the market that claim accuracy of >99% when used from the day of the expected period. [9] However, for some products, these claims cannot be replicated when tested either on clinical samples in the laboratory or when lay users perform the test.…”
Section: Introductionmentioning
confidence: 99%